Kabbalist and Communal Leader: Rabbi Yudel Rosenberg and the Canadian Jewish Community - Robinson, Ira (Canadian Jewish Studies / Études juives canadiennes, 1993)
The social, economic and religious pressures encountered by Eastern European Jews who emigrated to North America have been well documented. But focus on these areas has mostly failed to take into account the relationship between Orthodox Judaism and the process of adaptation to the New World. At the turn of the century, Orthodox rabbis, immigrants themselves, actively wrestled with the competing demands of Orthodox tradition and modern society. One such rabbi, Judah (Yudel) Rosenberg, brought with him to Canada a background combining both traditional Hasidism and secular learning. Rosenberg sought to draw the people closer to tradition by making it more accessible to them. Mysticism, especially, he viewed as the key to the preservation and regeneration of Judaism amongst a population that found it easier to make excuses than to follow the letter of religious law.